2009
DOI: 10.2215/cjn.01250209
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationships among Coronary Artery Calcification, Serum Phosphorus, and Kidney Function

Abstract: Background and objectives: Coronary artery calcification (CAC) is common in advanced chronic kidney disease (CKD), yet its onset and time course are uncertain. The study objective was to assess longitudinal relationships among CAC, kidney function, and traditional and putative cardiovascular disease (CVD) risk factors.Design, setting, participants, & measurements: This is a prospective cohort analysis from the Spokane Heart Study, a long-term observational study of community-dwelling adults who were assessed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 27 publications
2
73
0
5
Order By: Relevance
“…31 Various studies have evidenced the downregulation of miR-125b, miR-221, miR-222, miRhealthy adults have demonstrated that phosphorus levels at the upper limit of the normal range are independently associated with a greater likelihood and a more rapid progression of coronary artery calcium. 14, 15 In a study involving 439 multi-ethnic participants with moderate CKD but no clinical signs of CVD, Adeney et al reported that each 1 mg/dl (0.32 mmol/L) increment in phosphate level is strongly (P=0.002) and independently associated with a higher prevalence of calcification. 13 Actual therapy to manage hyperphosphatemia in endstage CKD includes, among others, oral phosphate binders such as calcium acetate, sevelamer or lanthanum.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…31 Various studies have evidenced the downregulation of miR-125b, miR-221, miR-222, miRhealthy adults have demonstrated that phosphorus levels at the upper limit of the normal range are independently associated with a greater likelihood and a more rapid progression of coronary artery calcium. 14, 15 In a study involving 439 multi-ethnic participants with moderate CKD but no clinical signs of CVD, Adeney et al reported that each 1 mg/dl (0.32 mmol/L) increment in phosphate level is strongly (P=0.002) and independently associated with a higher prevalence of calcification. 13 Actual therapy to manage hyperphosphatemia in endstage CKD includes, among others, oral phosphate binders such as calcium acetate, sevelamer or lanthanum.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…73,91,142 Hyperphosphatemia is also a risk factor for cardiovascular disease and mortality in chronic kidney disease. 39,48,72,193 Excessive FGF23 results in left ventricular hypertrophy via a klotho-independent mechanism, likely via the calcineurin-NFAT pathway. 53,168 However, recent work has suggested that FGF23 also regulates the number of Na þ -Cl -cotransporters in the distal tubules of the kidney.…”
Section: 119mentioning
confidence: 99%
“…17 Em outra coorte, que incluiu pacientes com média de idade mais elevada (48 anos), seguidos por 6 anos, o Pi sérico na primeira avaliação foi preditor tanto do surgimento de calcificação coronariana quanto da sua progressão (razão de chance: 1,54, p=0,002), embora não tenha havido correlação entre os dois parâmetros basais. 18 Recentemente, estudo realizado na Universidade de São Paulo avaliou a associação entre vários marcadores e a presença de doença coronariana em 290 pacientes clinicamente estáveis, com suspeita de doença arterial coronariana e TFG estimada superior a 60 ml/min. 19 Esta avaliação foi realizada tanto através da quantificação da calcificação coronariana através de tomografia computadorizada quanto pela presença de lesões obstrutivas à cineangiocoronariografia.…”
Section: Fosfatounclassified